ANALISIS DETERMINAN DAN PENGARUH STUNTING TERHADAP PRESTASI BELAJAR ANAK SEKOLAH DI KUPANG DAN SUMBA TIMUR, NTT - Intje Picauly; Sarci Magdalena Toy (Food and Nutrition Society of Indonesia, 2013)
The research was conducted to find out determinant factors that can cause the incidence of stunting and how it may affect elementary school children performance. The research areas were selected based on the difference access of nutrition information. Kabupaten Sumba Timur and Kota Kupang were selected as research areas. Related primary data was taken covering anthropometric index namely body height for age (HFA); weight for age (WFA), and weight for height (WFH), and academic school performances before and after research treatment. Other data was collected by interview using questionnaires. Regression analysis was used to know determinant factors that may bring about stunting. The results showed that determinant factors of stunting were family income, mother’s nutrition knowledge, child care practices, the history of infection, immunization, protein intake, and mother education. While, stunted elementary school children had low academic performances. The higher level of stunting is the lower academic performance of elementary school children.